From Land Capability to Food Security: Mapping Agricultural Spatial Directives in West Nusa Tenggara Using GIS-Based Analysis - Hidayat, Imam; Efani, Anthon; Pertiwi K, Maharani (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2025)
The designation of Sustainable Agricultural Land is a strategic initiative to counter rampant land conversion and soil degradation while supporting regional food security, particularly in West Nusa Tenggara Province, which relies heavily on its agricultural sector. This study aims to analyze the spatial suitability of Sustainable Agricultural areas based on biophysical conditions and the prevailing spatial planning policy. The analysis was conducted using Geographic Information System tools (ArcGIS Pro and QGis) with a spatial overlay approach, integrating land capacity indices, satellite-derived land use data, and biophysical parameters (e.g., slopes, soli type) alongside the spatial planning pattern map. The results show that most of the designated sustainable agricultural areas are aligned with agricultural land suitability parameters and contribute to regional food security objectives. The allocation of 282,062 hectares of sustainable agricultural area in West Nusa Tenggara Province was established through consensus between the provincial and municipal governments, as formally stipulated in Regional Regulation Number 5 of 2024. This policy not only provides a legal framework for protecting agricultural land from land use conversion but also serves as an integrative instrument for sustainable cross-sectoral development planning.